A regenerated silk fibroin-sodium hyaluronate gel for injection and a preparation method thereof

CN117771436BActive Publication Date: 2026-10-27NANJING SIYUAN MEDICAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311832872.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2026-10-27
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

通过物理方法交联制备的再生丝素蛋白凝胶存在弹性强度低、对热及辐照不稳定易出现胶水分离等问题;通过化学方法交联制备的再生丝素蛋白凝胶存在溶胀度低、对热和辐照不稳定易二次交联等问题,以及缺乏可注射的快速降解体内错位凝胶的酶

Benefits of technology

[0023]本发明提供了注射用再生丝素蛋白-透明质酸钠凝胶在制备软组织填充材料中的应用;优选地,所述软组织填充材料为组织再生医疗美容填充材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117771436B_ABST
    Figure CN117771436B_ABST
Patent Text Reader

Abstract

The application discloses a regenerated silk fibroin-sodium hyaluronate gel for injection and a preparation method thereof. The gel is crosslinked from 1.5-10 parts of regenerated silk fibroin, 1-3 parts of sodium hyaluronate and 0.9-2.5 parts of a crosslinking agent. The regenerated silk fibroin-sodium hyaluronate gel for injection prepared by the application has the advantages of high elastic modulus, good biocompatibility, good needle passability and long in-vivo degradation period. In particular, the regenerated silk fibroin in the gel can stimulate the regeneration of fibrocytes and collagen in tissues, prolongs the maintenance time of the effect of the filler, and is an innovative tissue regeneration medical cosmetic filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical aesthetics technology, specifically to an injectable regenerated silk fibroin-sodium hyaluronate gel and its preparation method. Background Technology

[0002] With the rapid development of the medical aesthetics industry in recent years, injectable soft tissue fillers have received increasing attention. Injecting soft tissue fillers can achieve facial cosmetic effects such as cheek augmentation, improvement of nasolabial folds, fuller jawline, firmer chin contour, and rhinoplasty. Currently, cross-linked sodium hyaluronate gel is the most commonly used soft tissue filler in the medical aesthetics industry, offering good immediate filling and shaping effects. However, because sodium hyaluronate degrades rapidly in the tissue environment, and because the single-material gel itself has low hardness and lacks the tissue regeneration function to stimulate cell growth and collagen production, patients typically need repeated injections every six months, significantly increasing treatment costs and causing adverse effects.

[0003] Silk fibroin, a major component of silk, is a natural high-molecular-weight block copolymer composed of 18 amino acids. These primarily include inactive glycine (43%) and alanine (30%), as well as active amino acids: serine (12.1%), tyrosine (5.3%), threonine (0.9%), glutamic acid (0.6%), aspartic acid (0.5%), and lysine (0.2%). The active amino acids can be chemically cross-linked for modification, enabling the widespread application of functional silk fibroin materials. Since its approval as a biomaterial by the U.S. Food and Drug Administration (FDA) in 1993, regenerated silk fibroin has been widely used in biomedicine and tissue engineering due to its excellent mechanical properties, good biocompatibility, biodegradability, and multifunctionality in structural adjustment. Regenerated silk fibroin can be processed into materials with different structures, such as solutions, silk membranes, microspheres / microparticles, hydrogels, scaffolds, and electrospun membranes, for applications in wound repair, drug delivery, tissue filling, and artificial organs.

[0004] In recent years, marketed regenerated silk fibroin products include Allergan's SERI surgical scaffold for abdominal wall reconstruction and plastic surgery. Sofregen in the US has developed SilkVoice, a natural silk fibroin injection for treating vocal cord medullolysis and vocal cord dysfunction. Suzhou Soho Biomaterials has developed a regenerated silk fibroin wound dressing for healing and repairing burns and scalds. Zhejiang Xingyue Biotechnology has developed silk fibroin membrane dressings and silk fibroin hydrogel dressings for donor site coverage and non-chronic wound coverage and care after laser treatment, respectively. Besides marketed products, some companies have also conducted clinical trials on products including regenerated silk fibroin bandages for ligament reconstruction, regenerated silk fibroin tissue mesh for inguinal hernia, regenerated silk fibroin sutures for oral surgery, and regenerated silk fibroin porous tissue regeneration scaffolds for meniscus cartilage repair. Currently, the development of regenerated silk fibroin into facial filler products is still in its infancy.

[0005] Silk fibroin hydrogels are an important form of regenerated silk fibroin materials. Due to their unique three-dimensional cross-linked structure, they exhibit excellent permeability and have attracted widespread attention for applications such as drug delivery carriers, fillers, cell culture scaffolds, and tissue engineering scaffolds. Regenerated silk fibroin gels prepared by physical cross-linking methods suffer from low elastic strength, instability to heat and radiation, and a tendency to separate. Regenerated silk fibroin gels prepared by chemical cross-linking methods suffer from low swelling degree, instability to heat and radiation, and a tendency to undergo secondary cross-linking, and lack injectable enzymes for rapidly degrading misaligned gels in vivo. Therefore, gels prepared by simply cross-linking silk fibroin have limitations in clinical application, production process selection, and production cost control.

[0006] In summary, considering the existing problems with silk fibroin gel, this study introduced sodium hyaluronate and regenerated silk fibroin gel to prepare a composite gel based on chemical cross-linking. This composite gel avoids the defects of cross-linking the two materials individually, and has moderate swelling degree, high elastic modulus, good needle penetration, and stability against heat and radiation. It can also be rapidly degraded by injecting sodium hyaluronate enzyme, and has many advantages such as wide clinical application range, diversified production process options, and controllable production costs. Summary of the Invention

[0007] To address the shortcomings of existing technologies, this invention provides an injectable regenerated silk fibroin-sodium hyaluronate gel and its preparation method.

[0008] The technical solution of the present invention is as follows: an injectable regenerated silk fibroin-sodium hyaluronate gel, wherein the gel is formed by cross-linking 1.5-10 parts of regenerated silk fibroin, 1-3 parts of sodium hyaluronate, and 0.9-2.5 parts of cross-linking agent under the action of a catalyst; wherein the mass ratio of regenerated silk fibroin to sodium hyaluronate is 2:1-6:1. The gel is prepared according to the following steps:

[0009] 1) Add the catalyst to purified water and stir to dissolve and stabilize the solution. Add the regenerated silk fibroin to the catalyst solution and stir to dissolve. Then add sodium hyaluronate to the regenerated silk fibroin-catalyst solution and stir to dissolve. Finally, add the cross-linking agent and stir evenly to carry out the cross-linking reaction.

[0010] 2) After the initial gel is cross-linked, it is crushed into small pieces, washed and swollen with phosphate buffer, crushed by sieving for the first time, granulated, washed, swollen, and centrifuged to remove the catalyst and free cross-linking agent, and then crushed by sieving for the second time to prepare gel particles.

[0011] 3) After adding phosphate buffer, the solution is filled into a pre-filled syringe and terminally sterilized to prepare an injectable soft tissue regeneration filler.

[0012] In some embodiments, the molecular weight of the regenerated silk fibroin is between 10 kDa and 300 kDa, preferably between 20 kDa and 200 kDa; and the molecular weight of the sodium hyaluronate is between 300 kDa and 1200 kDa, preferably between 600 kDa and 900 kDa.

[0013] In some embodiments, the mass ratio of the regenerated silk fibroin to sodium hyaluronate is 3:1 to 6:1, preferably 3:1 to 4:1.

[0014] In some embodiments, the crosslinking agent is one or more of ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, polypropylene glycol diglycidyl ether, diglycidyl ether, or divinyl sulfone, preferably 1,4-butanediol diglycidyl ether; the amount of the crosslinking agent is 1 / 3 to 1 / 10 of the total amount of regenerated silk fibroin and sodium hyaluronate, preferably 1 / 4 to 1 / 6.

[0015] In some embodiments, the catalyst is one or more of lithium bromide, calcium chloride, lithium hydroxide, and sodium hydroxide, with lithium bromide being preferred.

[0016] In some embodiments, the concentration of the catalyst in step 1) is 9-15 M, preferably 12 M; the concentration of regenerated silk fibroin is 2%-15% (w / v), preferably 10%-15% (w / v); and the concentration of sodium hyaluronate is 1%-10% (w / v), preferably 2%-5% (w / v).

[0017] In some embodiments, the crosslinking reaction temperature in step 1) is 18–35°C, preferably 22–28°C; and the crosslinking reaction time is 36–72 h, preferably 44–52 h.

[0018] In some embodiments, the pH of the phosphate buffer in steps 2) and 3) is 7.0 to 7.6, preferably 7.2 to 7.4; and the concentration of the phosphate buffer is 0.01M.

[0019] In some implementations, the screen aperture for the first sieve crushing in step 2) is 4 mm; the screen aperture for the second sieve crushing is 200-300 μm.

[0020] In some implementations, in step 2), the washing and swelling are performed twice before the first sieve crushing; and 6 to 8 times before the second sieve crushing; each washing and swelling time is 30 to 45 minutes.

[0021] In some embodiments, the amount of phosphate buffer added in step 3) is 20% to 40% of the weight of the gel particles.

[0022] In some implementations, the terminal sterilization in step 3) is selected from moist heat sterilization or irradiation sterilization.

[0023] This invention provides the application of injectable regenerated silk fibroin-sodium hyaluronate gel in the preparation of soft tissue filler materials; preferably, the soft tissue filler material is a tissue regeneration medical aesthetic filler material.

[0024] The beneficial effects of this invention are as follows: 1) Compared with traditional sodium hyaluronate self-crosslinking gel, the in vitro enzymatic degradation time of the regenerated silk fibroin-sodium hyaluronate gel is significantly prolonged. Under the same enzyme treatment conditions and the same time point, the remaining mass of the regenerated silk fibroin-sodium hyaluronate gel is significantly greater than that of the simply crosslinked sodium hyaluronate gel; furthermore, the elastic modulus of the regenerated silk fibroin-sodium hyaluronate gel is also significantly higher than that of the simply crosslinked sodium hyaluronate gel. Therefore, the composite crosslinking of regenerated silk fibroin and sodium hyaluronate can effectively prolong the degradation time of the gel, enhance its in vivo effect, and improve the effectiveness of the material; at the same time, it also broadens the application range of the material by increasing the elastic modulus of the gel.

[0025] 2) Compared with the simple chemical crosslinking of regenerated silk fibroin, the addition of HA increases the water absorption and water retention capacity of the gel, avoids the secondary crosslinking of regenerated silk fibroin under high temperature or irradiation, and improves the lubricity and needle-passing effect of the gel. Compared with the simple physical crosslinking of regenerated silk fibroin, the addition of HA and the selection of chemical crosslinking significantly improve the elastic modulus and strength of the gel and prolong the in vitro degradation time of the gel.

[0026] 3) Compared with existing silk fibroin-sodium hyaluronate composite gels, this invention directly dissolves silk fibroin and sodium hyaluronate raw materials in a catalyst solution for cross-linking reaction, without modifying the sodium hyaluronate. This makes the operation simpler and more controllable, and avoids potential safety hazards associated with gels. Furthermore, by adjusting the ratio of silk fibroin to sodium hyaluronate, this invention can obtain gels with different elastic moduli ranging from weak to strong, indicating broad application prospects for this material. The injectable regenerated silk fibroin-sodium hyaluronate gel prepared by this invention has advantages such as high elastic modulus, good biocompatibility, good needle penetration, and a long in vivo degradation period. In particular, the regenerated silk fibroin in the gel can also stimulate the regeneration of fibroblasts and collagen in tissues, prolonging the duration of the filler's effect. Attached Figure Description

[0027] Figure 1 Comparative Example 1: Photograph of the regenerated silk fibroin gel sample sterilized by moist heat

[0028] Figure 2 Comparative Example 1: Photograph of the irradiated sterilized sample of regenerated silk fibroin gel

[0029] Figure 3 Comparative Example 2: Viscoelasticity Test Results of Regenerated Silk Fiber Gel

[0030] Figure 4 Comparative Example 2: Shear viscosity test results of regenerated silk fibroin gel

[0031] Figure 5 Comparative Example 3: Viscoelasticity Test Results of Silk Fibroin-Hyaluronic Acid Composite Gel

[0032] Figure 6 Comparative Example 3: Shear viscosity test results of silk fibroin-hyaluronic acid composite gel

[0033] Figure 7 Example 1: Photograph of a sterilized sample of regenerated silk fibroin-sodium hyaluronate gel.

[0034] Figure 8 Example 1: Viscoelasticity test results of regenerated silk fibroin-sodium hyaluronate gel

[0035] Figure 9 Example 1: Results of Shear Viscosity Testing of Regenerated Silk Fibroin-Sodium Hyaluronate Gel

[0036] Figure 10 Example 1: Particle size detection results of regenerated silk fibroin-sodium hyaluronate gel

[0037] Figure 11 Example 1: Infrared spectrum of regenerated silk fibroin-sodium hyaluronate gel

[0038] Figure 12Example 2: Viscoelasticity test results of regenerated silk fibroin-sodium hyaluronate gel

[0039] Figure 13 Example 2: Particle size detection results of regenerated silk fibroin-sodium hyaluronate gel

[0040] Figure 14 Example 3: Viscoelasticity test results of regenerated silk fibroin-sodium hyaluronate gel

[0041] Figure 15 Example 4: Viscoelasticity test results of regenerated silk fibroin-sodium hyaluronate gel

[0042] Figure 16 Example 5: Viscoelasticity test results of regenerated silk fibroin-sodium hyaluronate gel

[0043] Figure 17 Example 6: Viscoelasticity Test Results of Regenerated Silk Fibroin-Sodium Hyaluronate Gel

[0044] Figure 18 Example 1: Results of in vitro enzymatic hydrolysis of regenerated silk fibroin-sodium hyaluronate gel Detailed Implementation

[0045] The following embodiments are intended to enable those skilled in the art to more fully understand the present invention, but are not intended to limit the invention to the scope of the embodiments described.

[0046] Comparative Example 1 (Chemical Crosslinking)

[0047] A method for preparing injectable regenerated silk fibroin gel: The preparation method includes the following steps:

[0048] a) Weigh 60g of regenerated silk fibroin, add it to 600ml of 12M lithium bromide solution and stir to dissolve. Then add 6ml of BDDE and stir evenly. Crosslink at 25℃ for 48h.

[0049] b) After the gel is broken into small pieces, it is washed twice with 6L of purified water for 30 minutes each time, and then granulated through a 4mm sieve. After granulation, the gel is first washed twice with 6L of purified water for 30 minutes each time; then washed with 6L of ethanol solution for 30 minutes each time; and finally washed three times with 6L of purified water for 30 minutes each time. The gel is collected by filtration and centrifugation to remove excess water, and then sieved twice through a 106μm sieve to obtain gel particles.

[0050] c) Add 30% purified water by weight of the gel particles; then add 5% mannitol by weight of the total weight of the gel and purified water, mix well, and fill with a 1ml pre-filled syringe. Sterilize by moist heat at 121℃ for 12min or by irradiation at 15KGY.

[0051] Figure 1 The image shows the regenerated silk fibroin gel prepared in this comparative example after being sterilized by moist heat at 121°C for 12 minutes. Figure 1 It can be seen that the regenerated silk fibroin gel undergoes glue separation after moist heat sterilization.

[0052] Figure 2 The image shows the regenerated silk fibroin gel prepared in this comparative example after sterilization by 15 kGY irradiation. Figure 2 It can be seen that the regenerated silk fibroin gel undergoes glue separation after irradiation sterilization, and the color of the pre-filled syringe changes.

[0053] Comparative Example 2 (Physical Crosslinking)

[0054] A method for preparing injectable regenerated silk fibroin gel: The preparation method includes the following steps:

[0055] a) Weigh 30g of regenerated silk fibroin, add it to 600ml of water for injection and stir to dissolve. Then add 6g of sodium oleate and stir to dissolve completely.

[0056] b) The above solution is filtered to remove insoluble particles, and then filtered again to remove bacteria to obtain the intermediate solution.

[0057] c) The intermediate solution was filled into a 1 mL pre-filled syringe under aseptic conditions.

[0058] d) After filling, the sample was incubated at 37°C for 48 hours to obtain regenerated silk fibroin gel.

[0059] Figure 3 The regenerated silk fibroin gel prepared in this comparative example is shown. At 25 ± 0.2 °C, a rheometer was used to perform frequency sweeps at selected frequencies from 0.1 Hz to 100 Hz to plot the coordinates of the viscous modulus G', elastic modulus G', and loss factor tan(δ) against frequency f. Figure 3 It can be seen that at a shear rate of 0.1 Hz, the elastic modulus G' is 277.4 Pa and the viscous modulus G” is 44.5 Pa. The results show that the viscoelasticity of the regenerated silk fibroin gel prepared by simple physical cross-linking is relatively poor.

[0060] Figure 4 The regenerated silk fibroin gel prepared in this comparative example is shown. It was tested at (25 ± 0.2) °C using a rheometer at a shear rate of 0.001 s⁻¹. -1 ~1000s -1 Perform a creep scan and plot the shear stress, viscosity η, and shear rate respectively. The coordinate graph. (From) Figure 4 It can be seen that at a shear rate of 0.001 s⁻¹ -1 ~1000s -1Below, the shear viscosity is ≥300 mPa·s.

[0061] Comparative Example 3 (CN102836465B Patent Formula and Process)

[0062] The silk fibroin-hyaluronic acid composite gel was prepared according to the method in Example 3 of patent CN102836465B. The specific steps are as follows:

[0063] a) Preparation of silk fibroin microspheres: 40g of silkworm silk was added to 2700ml of 0.2% sodium carbonate aqueous solution, and the mixture was heated in a water bath at 96-100℃ for 60min. After filtration, the filter cake was taken and the water bath was repeated 3 times. The filter cake from the last filtration was dried at 60℃ and then slowly dissolved in 200ml of 9mol / L lithium bromide aqueous solution. The mixture was heated in a water bath at 60℃ for 6h, and then centrifuged at 8000rpm for 5min. The supernatant was collected and placed in a dialysis bag (MW 8,000-14,000). Purified water was used as the dialysis fluid, and the mixture was magnetically stirred and dialyzed for three days. The retentate was collected and prepared into a 5% silk fibroin solution with purified water.

[0064] At 25°C, 5g of the above 5% silk fibroin solution was allowed to stand to form a white gel material. The gel material was homogenized at 24000rpm / min for 5min to obtain 5g of silk fibroin gel particles of different diameters. The particles were filtered and collected through a 200-mesh sieve. A small amount of the collected silk fibroin particles were weighed and dried to constant weight to determine the water content of the silk fibroin particles. The mass concentration of the silk fibroin particles was approximately 3.3%.

[0065] b) Preparation of silk fibroin-hyaluronic acid composite gel: 0.7g of sodium hyaluronate was dissolved in 7ml of 1% sodium hydroxide solution to prepare a 0.1g / ml sodium hyaluronate solution. 2.12g (0.07 / 0.033=2.12g) of silk fibroin particles were added to the sodium hyaluronate solution. After thorough mixing, 56μl of BDDE was added. After mixing evenly, the mixture was placed at 40℃ and allowed to stand for 5 hours to crosslink, forming a silk fibroin-hyaluronic acid composite gel material.

[0066] The above-mentioned silk fibroin-hyaluronic acid composite gel material was added to a dialysis bag with a MW 8,000-14,000 capacity. Using PBS buffer (pH 7.4) as the dialysis solution, dialysis was performed under magnetic stirring. The dialyzed composite gel material was homogenized at 24,000 rpm for 10 minutes, then squeezed through a 60-mesh sieve in a syringe. The composite gel particles were collected, sterilized by high-temperature autoclaving at 120°C for 15 minutes, and then aseptically dispensed into disposable syringes. This yields 35g of injectable silk fibroin-hyaluronic acid composite gel, suitable for subcutaneous injection.

[0067] Figure 5 The regenerated silk fibroin gel prepared in this comparative example is shown. At 25 ± 0.2 °C, a rheometer was used to perform frequency sweeps at shear rates from 0.1 Hz to 100 Hz to plot the coordinates of viscous modulus G', elastic modulus G', and loss factor tan(δ) against frequency f. Figure 5 It can be seen that at a shear rate of 0.1 Hz, the elastic modulus G' is 171.65 Pa and the viscous modulus G” is 26.98 Pa. The results show that the viscoelasticity of the silk fibroin-hyaluronic acid composite gel prepared by cross-linking silk fibroin gel microspheres and sodium hyaluronate is poor.

[0068] Figure 6 The silk fibroin-hyaluronic acid composite gel prepared in this comparative example is shown. It was tested at (25 ± 0.2) °C using a rheometer at a shear rate of 0.001 s⁻¹. -1 ~1000s -1 Perform a creep scan and plot the shear stress, viscosity η, and shear rate respectively. The coordinate graph. (From) Figure 6 It can be seen that at a shear rate of 0.001 s⁻¹ -1 ~1000s -1 Below, the shear viscosity is ≥180 mPa·s.

[0069] Example 1 (SF:HA = 3:1, SF concentration 10%)

[0070] A method for preparing injectable regenerated silk fibroin-sodium hyaluronate gel, the method comprising the following steps:

[0071] a) Weigh 60g of regenerated silk fibroin and add it to 600ml of 12M lithium bromide solution and stir to dissolve. Then add 20g of sodium hyaluronate and stir to dissolve. Add 16ml of BDDE (1,4-butanediol diglycidyl ether) and stir until homogeneous. Crosslink at 25℃ for 48h.

[0072] b) After the gel was broken into small pieces, it was washed twice with 6L PBS solution (pH 7.2-7.4) for 30 min each time. Then it was crushed by passing it through a 4 mm sieve. After crushing, the gel was washed six times with 6L PBS solution for 30 min each time. After the last three washings, it was centrifuged to remove free lithium bromide and BDDE. The collected centrifuged gel was passed through a 200 μm sieve twice to obtain gel particles.

[0073] c) The gel particles were mixed with PBS solution at 40% of the gel weight, stirred evenly, and then filled into a 1ml pre-filled syringe. The mixture was then sterilized by moist heat at 121℃ for 12min.

[0074] One gel sample was taken and tested using a 25G needle according to method 6.4 of YY / T 0962-2021. The average pushing force was 7.70 N, the maximum pushing force was 10.35 N, and the minimum pushing force was 6.24 N. 1.0 g of gel was taken and tested according to method 6.6 of YY / T 0962-2021 "Cross-linked Sodium Hyaluronate Gel for Plastic Surgery". The swelling ratio was 18.8.

[0075] Take an appropriate amount of gel and determine the osmotic pressure according to method 6.7 in YY / T 0962-2021; the osmotic pressure is 318 mOsmol / kg. Take an appropriate amount of gel and determine the pH value according to method 6.8 in YY / T 0962-2021; the pH value is 7.18.

[0076] Take an appropriate amount of gel, add sodium hyaluronate for hydrolysis, and then use a high-performance gas chromatography instrument to detect the residue of cross-linking agent BDDE. The results show that BDDE was not detected (limit is <2.0 μg / g).

[0077] Take an appropriate amount of gel and determine the lithium ion residue by inductively coupled plasma mass spectrometry (ICP-MS) according to 0412 of the Pharmacopoeia of the People's Republic of China (Part IV) (2020 edition). The lithium ion residue was 1.6 μg / g (limit <220 μg / g).

[0078] Take an appropriate amount of gel and determine the bromide ion residue according to the ion chromatography method in Pharmacopoeia of the People's Republic of China (Part IV) (2020 Edition) 0513. The residual bromide ion was 146 μg / g (limit is <2 mg / g).

[0079] Figure 7 The image shows the regenerated silk fibroin-sodium hyaluronate gel prepared in this embodiment after being sterilized by moist heat at 121°C for 12 minutes. Figure 7 It can be seen that the regenerated silk fibroin-sodium hyaluronate gel is a white to off-white gel with uniform properties and no glue separation.

[0080] Figure 8 The regenerated silk fibroin-sodium hyaluronate gel prepared in this embodiment is shown. At 25 ± 0.2 °C, a rheometer was used to perform frequency scanning at selected frequencies from 0.1 Hz to 100 Hz to plot the coordinates of viscous modulus G', elastic modulus G', and phase angle δ against frequency f. Figure 8 It can be seen that at a shear rate of 0.1 Hz, the elastic modulus G' is 1187.5 Pa and the viscous modulus G” is 161.3 Pa. The results show that the regenerated silk fibroin-sodium hyaluronate gel (3:1) has good viscoelasticity, which is much stronger than that of the purely physically cross-linked silk fibroin gel.

[0081] Figure 9The regenerated silk fibroin-sodium hyaluronate gel prepared in this embodiment is shown. It was tested at (25 ± 0.2) °C using a rheometer at a shear rate of 0.001 s⁻¹. -1 ~1000s -1 Perform a creep scan and plot the shear stress, viscosity η, and shear rate respectively. The coordinate graph. (From) Figure 9 It can be seen that at a shear rate of 0.001 s⁻¹ -1 ~1000s -1 Below, the shear viscosity is ≥300 mPa·s.

[0082] Figure 10 The particle size distribution of the regenerated silk fibroin-sodium hyaluronate gel prepared in this embodiment is shown. Figure 10 It can be seen that the regenerated silk fibroin-sodium hyaluronate gel particles prepared in this embodiment have a uniform particle size distribution, with d(0.5) being 285.6 μm and d(0.9) being 548.4 μm.

[0083] Figure 11 The infrared spectrum of the regenerated silk fibroin-sodium hyaluronate gel prepared in this embodiment is shown. Figure 11 It can be seen that the measured Fourier transform infrared (FT-IR) band of the gel prepared in this embodiment is at 1700 cm⁻¹. -1 ~1600cm -1 1590cm -1 ~1460cm -1 1450cm -1 ~1400cm -1 1350cm -1 ~1300cm -1 1280cm -1 ~1190cm -1 1000cm -1 ~900cm -1 A characteristic peak exists at this location.

[0084] Example 2 (SF:HA = 3:1, SF concentration 10%)

[0085] A method for preparing injectable regenerated silk fibroin-sodium hyaluronate gel, the method comprising the following steps:

[0086] a) Weigh 60g of regenerated silk fibroin and add it to 600ml of 12M lithium bromide solution and stir to dissolve. Then add 20g of sodium hyaluronate and stir to dissolve. Add 16ml of BDDE and stir evenly. Crosslink at 25℃ for 48h.

[0087] b) After the gel was broken into small pieces, it was washed twice with 6L PBS solution (pH 7.2-7.4) for 45 min each time. Then it was crushed by passing it through a 4 mm sieve. After crushing, the gel was washed five times with 6L PBS solution for 45 min each time. After the last three washings, it was centrifuged to remove free lithium bromide and BDDE. The collected centrifuged gel was passed through a 300 μm sieve twice to obtain gel particles.

[0088] c) The gel particles were mixed with PBS solution at 40% of the gel weight, stirred evenly, and then filled into a 1ml pre-filled syringe. The mixture was then sterilized by moist heat at 121℃ for 12min.

[0089] Figure 12 The regenerated silk fibroin-sodium hyaluronate gel prepared in this embodiment is shown. At 25 ± 0.2 °C, a rheometer was used to perform frequency scanning at shear rates from 0.1 Hz to 100 Hz to plot the coordinates of the viscous modulus G', elastic modulus G', and loss factor tan(δ) against frequency f. Figure 12 It can be seen that at a shear rate of 0.1 Hz, the elastic modulus G' is 2156 Pa and the viscous modulus G” is 277.9 Pa. The results show that the regenerated silk fibroin-sodium hyaluronate gel (3:1) prepared by passing through a 300 μm sieve has good viscoelasticity, and its viscoelasticity is stronger than that of the gel prepared by passing through a 200 μm sieve.

[0090] Figure 13 The particle size distribution of the regenerated silk fibroin-sodium hyaluronate gel prepared in this embodiment is shown. Figure 13 It can be seen that the regenerated silk fibroin-sodium hyaluronate gel particles prepared in this embodiment have a uniform particle size distribution, with d(0.5) being 721.4 μm and d(0.9) being 1353.8 μm.

[0091] Example 3 (SF:HA = 6:1, SF concentration 15%)

[0092] A method for preparing injectable regenerated silk fibroin-sodium hyaluronate gel, the method comprising the following steps:

[0093] a) Weigh 90g of regenerated silk fibroin and add it to 600ml of 12M lithium bromide solution and stir to dissolve. Then add 15g of sodium hyaluronate and stir to dissolve. Add 21ml of BDDE and stir until homogeneous. Crosslink at 25℃ for 48h.

[0094] b) After the gel was broken into small pieces, it was washed twice with 6L PBS solution (pH 7.2-7.4) for 30 min each time. Then it was crushed by passing it through a 4 mm sieve. After crushing, the gel was washed six times with 6L PBS solution for 30 min each time. After the last three washings, it was centrifuged to remove free lithium bromide and BDDE. The collected centrifuged gel was passed through a 200 μm sieve twice to obtain gel particles.

[0095] c) The gel particles were mixed with PBS solution at 40% of the gel weight, stirred evenly, and then filled into a 1ml pre-filled syringe. The mixture was then sterilized by moist heat at 121℃ for 12min.

[0096] Figure 14 The regenerated silk fibroin-sodium hyaluronate gel prepared in this embodiment is shown. At 25 ± 0.2 °C, a rheometer was used to perform frequency scanning at selected frequencies from 0.1 Hz to 100 Hz to plot the coordinates of viscous modulus G', elastic modulus G', and frequency f. Figure 14 It can be seen that at a shear rate of 0.1 Hz, the elastic modulus G' is 2972.8 Pa and the viscous modulus G” is 236.4 Pa. The results show that the regenerated silk fibroin-sodium hyaluronate gel (6:1) has good viscoelasticity, and the viscoelasticity of the finished product increases significantly with the increase of the amount of regenerated silk fibroin added.

[0097] Example 4 (SF:HA = 4:1, SF concentration 10.7%)

[0098] A method for preparing injectable regenerated silk fibroin-sodium hyaluronate gel, the method comprising the following steps:

[0099] a) Weigh 64g of regenerated silk fibroin and add it to 600ml of 12M lithium bromide solution and stir to dissolve. Then add 16g of sodium hyaluronate and stir to dissolve. Add 16ml of BDDE and stir until homogeneous. Crosslink at 25℃ for 48h.

[0100] b) After the gel was broken into small pieces, it was washed twice with 6L PBS solution (pH 7.2-7.4) for 30 min each time. Then it was crushed by passing it through a 4 mm sieve. After crushing, the gel was washed six times with 6L PBS solution for 30 min each time. After the last three washings, it was centrifuged to remove free lithium bromide and BDDE. The collected centrifuged gel was passed through a 200 μm sieve twice to obtain gel particles.

[0101] c) The gel particles were mixed with PBS solution at 40% of the gel weight, stirred evenly, and then filled into a 1ml pre-filled syringe. The mixture was then sterilized by moist heat at 121℃ for 12min.

[0102] Figure 15The regenerated silk fibroin-sodium hyaluronate gel prepared in this embodiment is shown. At 25 ± 0.2 °C, a rheometer was used to perform frequency scanning at selected frequencies from 0.1 Hz to 100 Hz to plot the coordinates of viscous modulus G', elastic modulus G', and frequency f. Figure 15 It can be seen that at a shear rate of 0.1 Hz, the elastic modulus G' is 1916.8 Pa and the viscous modulus G” is 124.8 Pa. The results show that the regenerated silk fibroin-sodium hyaluronate gel (4:1) has good viscoelasticity, and the viscoelasticity of the finished product increases significantly with the increase of the amount of regenerated silk fibroin added.

[0103] Example 5 (SF:HA = 2:1, SF concentration 10%)

[0104] A method for preparing injectable regenerated silk fibroin-sodium hyaluronate gel, the method comprising the following steps:

[0105] a) Weigh 60g of regenerated silk fibroin and add it to 600ml of 12M lithium bromide solution and stir to dissolve. Then add 30g of sodium hyaluronate and stir to dissolve. Add 18ml of BDDE and stir evenly. Crosslink at 25℃ for 48h.

[0106] b) After the gel was broken into small pieces, it was washed twice with 6L PBS solution (pH 7.2-7.4) for 30 min each time. Then it was crushed by passing it through a 4 mm sieve. After crushing, the gel was washed six times with 6L PBS solution for 30 min each time. After the last three washings, it was centrifuged to remove free lithium bromide and BDDE. The collected centrifuged gel was passed through a 200 μm sieve twice to obtain gel particles.

[0107] c) The gel particles were mixed with PBS solution at 40% of the gel weight, stirred evenly, and then filled into a 1ml pre-filled syringe. The mixture was then sterilized by moist heat at 121℃ for 12min.

[0108] Figure 16 The regenerated silk fibroin-sodium hyaluronate gel prepared in this embodiment is shown. At 25 ± 0.2 °C, a rheometer was used to perform frequency scanning at selected frequencies from 0.1 Hz to 100 Hz to plot the coordinates of viscous modulus G', elastic modulus G', and frequency f. Figure 16 It can be seen that at a shear rate of 0.1 Hz, the elastic modulus G' is 588.2 Pa and the viscoelastic modulus G” is 78.3 Pa. The results show that the viscoelasticity of the regenerated silk fibroin-sodium hyaluronate gel (2:1) is slightly poor. As the amount of regenerated silk fibroin added decreases, the viscoelasticity of the finished product decreases significantly.

[0109] Example 6 (SF:HA = 0.5:1, SF concentration 2.5%)

[0110] A method for preparing injectable regenerated silk fibroin-sodium hyaluronate gel, the method comprising the following steps:

[0111] d) Weigh 15g of regenerated silk fibroin and add it to 600ml of 12M lithium bromide solution and stir to dissolve. Then add 30g of sodium hyaluronate and stir to dissolve. Add 9ml of BDDE and stir evenly. Crosslink at 25℃ for 48h.

[0112] e) After the gel is broken into small pieces, it is washed twice with 6L PBS solution (pH 7.2-7.4) for 30 min each time; then it is crushed by passing it through a 4 mm sieve. After crushing, the gel is washed six times with 6L PBS solution for 30 min each time. After the last three washings, it is centrifuged to remove free lithium bromide and BDDE; the collected centrifuged gel is passed through a 200 μm sieve twice to obtain gel particles.

[0113] f) The gel particles were mixed with PBS solution at 40% of the gel weight, stirred evenly, and then filled into a 1ml pre-filled syringe. The mixture was then sterilized by moist heat at 121℃ for 12min.

[0114] Figure 17 The regenerated silk fibroin-sodium hyaluronate gel prepared in this embodiment is shown. At 25 ± 0.2 °C, a rheometer was used to perform frequency scanning at selected frequencies from 0.1 Hz to 100 Hz to plot the coordinates of viscous modulus G', elastic modulus G', and frequency f. Figure 17 It can be seen that at a shear rate of 0.1 Hz, the elastic modulus G' is 289.01 Pa and the viscoelastic modulus G” is 47.49 Pa. The results show that the viscoelasticity of the regenerated silk fibroin-sodium hyaluronate gel (0.5:1) is poor, and the viscoelasticity of the finished product decreases significantly with the reduction of the amount of regenerated silk fibroin added.

[0115] Example 7 (SF:HA = 10:1, SF concentration 16.7%)

[0116] A method for preparing injectable regenerated silk fibroin-sodium hyaluronate gel, the method comprising the following steps:

[0117] a) Weigh 100g of regenerated silk fibroin and add it to 600ml of 12M lithium bromide solution and stir to dissolve. Then add 10g of sodium hyaluronate and stir to dissolve. Add 22ml of BDDE and stir evenly. Crosslink at 25℃ for 48h.

[0118] b) After the gel was broken into small pieces, it was washed twice with 6L PBS solution (pH 7.2-7.4) for 30 min each time. Then it was crushed by passing it through a 4 mm sieve. After crushing, the gel was washed six times with 6L PBS solution for 30 min each time. After the last three washings, it was centrifuged to remove free lithium bromide and BDDE. The collected centrifuged gel was passed through a 200 μm sieve twice to obtain gel particles.

[0119] c) The gel particles were mixed with PBS solution at 40% of the gel weight, stirred evenly, and then filled into a 1ml pre-filled syringe. The mixture was then sterilized by moist heat at 121℃ for 12min.

[0120] After moist heat sterilization, the gel underwent secondary cross-linking to a certain extent, making sample passage difficult. Blockage occurred when using a 23G needle, and the maximum pushing force was >60N according to method 6.4 of YY / T 0962-2021. Therefore, the gel prepared in this example is unsuitable for clinical injection filling.

[0121] Test Example 1: In vitro anti-degradation ability test

[0122] The regenerated silk fibroin-sodium hyaluronate gel prepared in Example 1 and the commercially available Restylane 2 cross-linked sodium hyaluronate gel were degraded in vitro using sodium hyaluronate enzyme. The in vitro anti-enzymatic hydrolysis ability of the composite gel and the simple cross-linked sodium hyaluronate gel was determined by observing the weight of the remaining gel at different time points.

[0123] The specific implementation plan is as follows:

[0124] a) Preparation of hyaluronidase solution (1500 units / ml) (prepare immediately before use)

[0125] Accurately weigh 20 mg of hyaluronidase (1500 units / mg) into a 20 ml volumetric flask, dilute to the mark with 0.9% sodium chloride solution, and shake well to obtain a hyaluronidase solution with a concentration of (1500 units / ml).

[0126] b) Sample preparation

[0127] Take 16 centrifuge tubes and label them 1-1 to 1-7 and 2-1 to 2-7 respectively. Accurately weigh 5g of regenerated silk fibroin-sodium hyaluronate gel into centrifuge tubes 1-1 to 1-7, and accurately weigh 5g of cross-linked silk fibroin sodium gel into centrifuge tubes 2-1 to 2-7. Centrifuge all 8 tubes in a centrifuge for 3 minutes (2500g), and collect all the gel from the bottom of the tubes (observe whether there is liquid on the surface; if so, remove it with a pipette).

[0128] c) Enzymatic hydrolysis

[0129] Add 2 ml of 0.9% sodium chloride solution to centrifuge tubes 1-1 and 2-1 as samples at time 0. Add 2 ml of hyaluronidase solution (1500 units / ml) to centrifuge tubes 1-2 to 1-7 and 2-2 to 2-7. Gently shake to ensure that the hyaluronidase comes into full contact with the gel, avoiding gel formation on the centrifuge tube walls. After visually mixing, place all the centrifuge tubes in a 37°C oven.

[0130] d) Sampling and weighing

[0131] Centrifuge tubes 1-2 to 1-7 and 2-2 to 2-7 were removed from the oven at 1h, 2h, 3h, 4h, 6h, and 8h, respectively. 6ml of 0.9% sodium chloride solution was added, the solution was shaken to mix the contents, and the mixture was filtered through a 0.22μm filter membrane. The filtrate was collected in a vacuum flask, and the centrifuge tubes were washed with a total of 90ml of 0.9% sodium chloride solution in several portions. The filter cake was then weighed. Sample processing at 0h was the same as above.

[0132] e) Calculation

[0133] With the sample weight at time 0 as 100%, the remaining gel weight (%) = (sample weight at different time points / sample weight at time 0) × 100%. Results are as follows: Figure 18 As shown, the in vitro anti-enzymatic degradation ability of regenerated silk fibroin-sodium hyaluronate gel is significantly better than that of simple cross-linked sodium hyaluronate gel.

[0134] Test Example 2: Short-term biological experiment

[0135] The regenerated silk fibroin-sodium hyaluronate gel prepared in Example 1 was subjected to the extraction method (MTT method) specified in GB / T 16886.5-2017 "Biological Evaluation of Medical Devices Part 5: In Vitro Cytotoxicity Tests", with cell culture medium as the extraction medium. The results showed that the gel was non-cytotoxic under the MTT cytotoxicity test conditions.

[0136] The regenerated silk fibroin-sodium hyaluronate gel prepared in Example 1 was used to assess the potential of the test sample to induce skin sensitization in guinea pigs under the test conditions, according to the skin sensitization test (maximum dose method) recommended in GB / T 16886.10-2017 "Biological evaluation of medical devices - Part 10: Irritation and skin sensitization tests". The results showed that the test sample did not induce skin sensitization, and the incidence of positive challenge results was 0%.

[0137] The regenerated silk fibroin-sodium hyaluronate gel prepared in Example 1 was subjected to a biocompatibility test on the sample extract according to the intradermal reaction requirements recommended in GB / T 16886.10-2017 "Biological Evaluation of Medical Devices Part 10: Irritation and Skin Sensitization Tests". The test sample was extracted with a polar extract (0.9% sodium chloride injection) and a non-polar extract (cottonseed oil). The resulting extracts were administered to New Zealand albino rabbits via intradermal injection, and the potential for irritation under the test conditions was evaluated. The results showed that the final score for the intradermal reaction of the polar extract was 0.00; the final score for the intradermal reaction of the non-polar extract was also 0.00, indicating a good intradermal reaction.

[0138] The regenerated silk fibroin-sodium hyaluronate gel prepared in Example 1 was tested according to the methods recommended in GB / T 16886.11-2021 "Biological Evaluation of Medical Devices Part 11: Systemic Toxicity Testing". The sample was directly used as the test solution and injected subcutaneously into mice. The results showed that the test sample had no acute systemic toxicity in mice.

[0139] The regenerated silk fibroin-sodium hyaluronate gel prepared in Example 1 was tested according to the methods recommended in GB / T 16886.11-2021 "Biological Evaluation of Medical Devices Part 11: Systemic Toxicity Testing". The test sample was extracted with 0.9% sodium chloride injection solution, and the supernatant was injected into the ear vein of New Zealand rabbits. The results showed that the pyrogen test of the test sample gel met the requirements, and there was no pyrogenic effect of the material.

Claims

1. An injectable regenerated silk fibroin-sodium hyaluronate gel, wherein the gel is formed by cross-linking 1.5-10 parts of regenerated silk fibroin, 1-3 parts of sodium hyaluronate, and 0.9-2.5 parts of cross-linking agent under the action of a catalyst; wherein the mass ratio of regenerated silk fibroin to sodium hyaluronate is 3:1-4:1; the gel is prepared according to the following steps: 1) Add the catalyst to purified water and stir to dissolve and stabilize the solution. Add the regenerated silk fibroin to the catalyst solution and stir to dissolve. Then add sodium hyaluronate to the regenerated silk fibroin-catalyst solution and stir to dissolve. Finally, add the cross-linking agent and stir evenly to carry out the cross-linking reaction. 2) After the initial gel is crushed into small pieces, it is washed and swollen with phosphate buffer solution, then crushed by sieving for the first time. After granulation, it is washed, swollen, and centrifuged to remove the catalyst and free crosslinking agent. Then it is crushed by sieving for the second time to prepare gel particles. 3) After adding phosphate buffer, the pre-filled syringe is filled and terminally sterilized to prepare an injectable soft tissue regeneration filler; The molecular weight of the regenerated silk fibroin is between 20 kDa and 200 kDa; the molecular weight of the sodium hyaluronate is between 600 kDa and 900 kDa. The crosslinking agent is 1,4-butanediol diglycidyl ether; the amount of the crosslinking agent added is 1 / 4 to 1 / 6 of the total amount of regenerated silk fibroin and sodium hyaluronate; the catalyst is lithium bromide. In step 1), the catalyst concentration is 12M; the concentration of regenerated silk fibroin is 10%~15% (w / v); the concentration of sodium hyaluronate is 2%~5% (w / v); the crosslinking reaction temperature in step 1) is 22~28℃; and the crosslinking reaction time is 44~52h. In steps 2) and 3), the pH of the phosphate buffer solution is 7.0-7.6, preferably 7.2-7.4; the concentration of the phosphate buffer solution is 0.01M. In step 2), the screen mesh size for the first sieve crushing is 4 mm; the screen mesh size for the second sieve crushing is 200~300 μm; in step 2), the first sieve crushing is washed and swollen twice; the second sieve crushing is washed and swollen 6~8 times; each washing and swelling time is 30~45 min. In step 3), the amount of phosphate buffer solution added is 20% to 40% of the weight of the gel particles; In step 3), terminal sterilization is performed using either moist heat sterilization or irradiation sterilization.

2. The application of the injectable regenerated silk fibroin-sodium hyaluronate gel according to claim 1 in the preparation of soft tissue filler materials; wherein the soft tissue filler material is a tissue regeneration medical aesthetic filler material.

Citation Information

Patent Citations

  • Silk-fibroi and hyaluronic-acid (HA) composite gel for injection and preparation and application thereof

    CN102836465B

  • Silk-fibroi and hyaluronic-acid (HA) composite gel for injection and preparation and application thereof

    CN102836465A

  • Chemical crosslinking hydrogel and microsphere, and preparation method and application thereof

    CN113549227A